Screening Emodin Derivatives as DPP-4 Inhibitor Candidates: In Silico and In Vitro Assessment - Azkiyah, Dina; Syahbirin, Gustini; Firdayani, Firdayani; Sugita, Purwantiningsih (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease distinguished by disrupted glucose metabolism, causing elevated blood sugar levels. One of the latest therapeutic strategies involves inhibiting dipeptidyl peptidase-4 (DPP-4) to regulate glucose metabolism. Emodin, a bioactive compound, has shown potential as a DPP-4 inhibitor, but its efficacy requires further research. This study aims to identify and assess emodin and its derivatives as potential DPP-4 inhibitors through a comprehensive in silico and in vitro analysis. Molecular docking analysis revealed that 3-ρ-toluoyl emodin (ρTE) had the lowest binding energy (-111.4 kcal/mol) among the tested compounds. Furthermore, in vitro testing showed consistent results in silico, indicating that ρTE had significant inhibitory activity with an IC50 value of 1.37 μM. Pharmacokinetic and physicochemical evaluations confirmed ρTE’s potential as a safe antidiabetic drug candidate. The research findings indicate that ρTE holds potential as a promising drug candidate for further development.